2017
DOI: 10.1111/jav.01521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light‐level geolocators on apparent survival of two highly aerial swift species

Abstract: Light-level geolocators are currently widely used to track the migration of smallsized birds, but their potentially detrimental effects on survival of highly aerial species have been poorly investigated so far. We recorded capture-recapture histories of 283 common swifts Apus apus and 107 pallid swifts Apus pallidus breeding in 14 colonies in Italy, Spain, Sweden and Switzerland that were equipped with 10 different types of geolocators ('geolocator birds'), and compared their survival with that of, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 40 publications
1
34
3
Order By: Relevance
“…We cannot rule out the possibility that stalkless units or an alternative tag or harness design would mitigate the effects that we observed. One study with a moderate sample size on another small warbler found no effect of stalks on return rates [7], but larger studies on other species have sometimes found moderate effects of stalk length or stalk presence on return rates [13, 35].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule out the possibility that stalkless units or an alternative tag or harness design would mitigate the effects that we observed. One study with a moderate sample size on another small warbler found no effect of stalks on return rates [7], but larger studies on other species have sometimes found moderate effects of stalk length or stalk presence on return rates [13, 35].…”
Section: Discussionmentioning
confidence: 99%
“…NLMMs allow for a large flexibility in the parameterization of both the fixed and the random part of the model, but this flexibility also makes it hard to assess the optimal structure of the model. Following a similar procedure described in Sicurella et al ( 2014 ) and Morganti et al ( 2017 ), we therefore ran preliminary analyses to assess which parameter(s) showed variability according to soil pH (entered as a three-level factor), and which parameter(s) showed large among-individual variability, and should therefore be included as random effect(s). These preliminary analyses were run by first interpolating logistic curves to data of each plant separately and noting the estimated value of individual parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the NLMM allowed A, k and i to vary with pH, but not m . We also plotted the range of parameters from curves fitted to individual plants and, in the NLMMs, allowed for random variation in those parameters which, at a visual inspection, showed large heterogeneity (see also Sicurella et al, 2014 ; Morganti et al, 2017 ). Finally, we controlled for heteroscedasticity by assuming a variation of the variance with time according to an exponential function, as suggested in Oswald et al ( 2012 ) in all models except for that of leaf width because a model assuming homoscedasticity had a lower AICc value, indicating a better fit (details not shown).…”
Section: Methodsmentioning
confidence: 99%
“…It is currently not established in what ways a reduced recapture rate may be associated with the movement pattern of the recaptured birds, but we have not found any apparent differences in the tracks between the sites included here (cf. Morganti et al 2017). All but one pallid swift returned to their nests after tag deployment as reflected by the repeated shadings during day-light hours in the light-data, indicating that the birds did not abandon the nests as an effect of handling.…”
Section: Trapping and Deploymentmentioning
confidence: 99%